2003
DOI: 10.1109/tip.2003.819226
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated image processing on FPGAs

Abstract: The Cameron project has developed a language called single assignment C (SA-C), and a compiler for mapping image-based applications written in SA-C to field programmable gate arrays (FPGAs). The paper tests this technology by implementing several applications in SA-C and compiling them to an Annapolis Microsystems (AMS) WildStar board with a Xilinx XV2000E FPGA. The performance of these applications on the FPGA is compared to the performance of the same applications written in assembly code or C for an 800 MHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(44 citation statements)
references
References 22 publications
0
41
0
3
Order By: Relevance
“…We need to improve its throughput and latency, which can be accomplished by simultaneously processing multiple adjacent rows [26]. This requires multiple pixels to be input per clock cycle and exploits the fact that the windows for vertically adjacent outputs overlap significantly, as can be seen in Fig.…”
Section: B Unfolding Retimed Architecturementioning
confidence: 99%
“…We need to improve its throughput and latency, which can be accomplished by simultaneously processing multiple adjacent rows [26]. This requires multiple pixels to be input per clock cycle and exploits the fact that the windows for vertically adjacent outputs overlap significantly, as can be seen in Fig.…”
Section: B Unfolding Retimed Architecturementioning
confidence: 99%
“…Moreover, FPGAs are generally the first devices to be implemented on the state-of-art silicon technology. Therefore, even if FPGAs were initially created for developing little glue-logic, they currently often represent the core of various systems in different fields (e.g., [9][10][11][12][13][14] The software environment for friendly designing, simulating and testing is Altera's Quartus II™. Fig.…”
Section: Fpga-based Hardware Implementationmentioning
confidence: 99%
“…The most important idea behind the smart camera architecture is to collect video data and then analyze, interpret and reduce the information before it leaves the camera. To ensure realtime processing, the computation architecture used in the camera traditionally are VLIW processor and more recently it has been shown that programmable logic (FPGAs) are more efficient in implementing RTVPS systems [4] [5]. Based on this fact, we have selected FPGA as the target architecture for the design environment presented in this paper.…”
Section: Introductionmentioning
confidence: 99%